PENGARUH SHOPPING LIFESTYLE, USIA DAN GENDER TERHADAP IMPULSE BUYING PRODUK FASHION (SURVEY PADA KONSUMEN PRODUK FASHION DI MALANG TOWN SQUARE (MATOS) - Putra, Frengki Kriswardana (Manajemen Bisnis, 2016)
The purpose of this study was to examine the influence of shopping lifestyle, age and gender on impulse buying fashion products partially. The population in this study are all consumers who purchase fashion products at Malang Town Square (Matos), located on Jl. Veterans no. 2 Malang. The sample in this study is that consumers fashion products at Malang Town Square (Matos). The sampling method used was purposive sampling method.The analytical tool used to determine the effect of shopping lifestyle, age and gender on impulse buying fashion products at Malang Town Square (Matos) is Factor Analysis and Regression with dummy variables. Hypothesis testing is performed using the t test and the test of the coefficient of determination.Results of Multiple Linear Regression with dummy variables indicating that the shopping lifestyle and gender positive and significant effect on impulse buying fashion products at Malang Town Square (Matos), while age negatively affect impulse buying fashion products at Malang Town Square (Matos). The results of the t test showed that the variables that have the greatest influence is age